2015
DOI: 10.1002/ijch.201500052
|View full text |Cite
|
Sign up to set email alerts
|

Natural Quorum Sensing Inhibitors – Small Molecules, Big Messages

Abstract: Due to the increasing emergence of antibiotic resistant bacterial strains within the past few decades, bacterial infections in general – and hospital‐borne infections, in particular – have become increasingly difficult to fight. It is therefore crucial to find new strategies to fight pathogenic bacteria. Targeted inhibition of quorum sensing (QS) presents a promising alternative. QS is a cell density‐dependent signaling pathway used for intra‐ and interspecies coordination of gene expression. In many bacteria,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(16 citation statements)
references
References 94 publications
0
14
0
2
Order By: Relevance
“…Several antagonist peptides have been identified among natural compounds or designed to quench Gram-positive bacteria and many QSIs, mainly targeting Gram-negative QS and AI-2 mediated QS, have also been reported (Tang and Zhang, 2014 ; Singh et al, 2016 ). Such compounds can be natural products, like polyphenols isolated from tea or honey, ajoene from garlic, eugenol from clove or many others produced by marine organisms and fungi (Tang and Zhang, 2014 ; Delago et al, 2016 ), or they can be synthetic, such as 5-fluorouracil (5-FU) or azithromycin (Ueda et al, 2009 ; Swatton et al, 2016 ). Many QQ enzymes and macromolecules (Amara et al, 2011 ; Fetzner, 2015 ) as well as natural or synthetic QSIs (Dembitsky et al, 2011 ; Galloway et al, 2011 ; Stevens et al, 2011 ; Kalia, 2013 ; Delago et al, 2016 ) have been reported to date and exhaustively reviewed.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several antagonist peptides have been identified among natural compounds or designed to quench Gram-positive bacteria and many QSIs, mainly targeting Gram-negative QS and AI-2 mediated QS, have also been reported (Tang and Zhang, 2014 ; Singh et al, 2016 ). Such compounds can be natural products, like polyphenols isolated from tea or honey, ajoene from garlic, eugenol from clove or many others produced by marine organisms and fungi (Tang and Zhang, 2014 ; Delago et al, 2016 ), or they can be synthetic, such as 5-fluorouracil (5-FU) or azithromycin (Ueda et al, 2009 ; Swatton et al, 2016 ). Many QQ enzymes and macromolecules (Amara et al, 2011 ; Fetzner, 2015 ) as well as natural or synthetic QSIs (Dembitsky et al, 2011 ; Galloway et al, 2011 ; Stevens et al, 2011 ; Kalia, 2013 ; Delago et al, 2016 ) have been reported to date and exhaustively reviewed.…”
Section: Introductionmentioning
confidence: 99%
“…Such compounds can be natural products, like polyphenols isolated from tea or honey, ajoene from garlic, eugenol from clove or many others produced by marine organisms and fungi (Tang and Zhang, 2014 ; Delago et al, 2016 ), or they can be synthetic, such as 5-fluorouracil (5-FU) or azithromycin (Ueda et al, 2009 ; Swatton et al, 2016 ). Many QQ enzymes and macromolecules (Amara et al, 2011 ; Fetzner, 2015 ) as well as natural or synthetic QSIs (Dembitsky et al, 2011 ; Galloway et al, 2011 ; Stevens et al, 2011 ; Kalia, 2013 ; Delago et al, 2016 ) have been reported to date and exhaustively reviewed. Patents associated with these compounds (Pan and Ren, 2009 ; Romero et al, 2012 ; Jiang and Li, 2013 ) as well as routes to access novel molecules (Scutera et al, 2014 ) have also been discussed.…”
Section: Introductionmentioning
confidence: 99%
“…Taken together, interfering this mechanism would have an astounding impact over the bacterial resistance and its control (Uroz et al, 2009 ; Kalia, 2015 ). Numerous studies have been published related to quorum sensing inhibitors (QSIs) which rationalize the capability of this strategy (Ren et al, 2005 ; Rasmussen and Givskov, 2006 ; Ni et al, 2008 ; Kalia, 2013 ; Brackman and Coenye, 2015 ; Coughlan et al, 2016 ; Delago et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…They include halogenated furanones, ( 56 ) [44,109], betonicine ( 57 ), cis -betonicine ( 58 ), floridoside ( 59 ), and isethionic acid ( 60 ) (Figure 11). They display an inhibition activity on QS mechanisms mediated by C 8 -AHL lactone and the TraR transcriptional activator protein [38,50,51,110]. ICR-FT/MS analysis revealed the presence of 2-dodecanoyloxyethanesulfonate ( 61 ) (Figure 11), in Asparagopsis taxiformis , as the lead molecule responsible for QSI activity based on Serratia liquefacien s MG44 and C. violaceum CV026 bioassays.…”
Section: Qsi From Marine Algaementioning
confidence: 99%